Nurses and care workers' perceptions of their nurse-patient therapeutic relationship in private general hospitals, Gauteng, South Africa - Anna E. van den Heever; Marie Poggenpoel; Chris P.H. Myburgh (AOSIS, 2013)
Facilitation of a therapeutic relationship is an essential skill in nursing, particularly in mental-health care. Nurses and care workers in private general hospitals are exposed to the emotional effects of physical illness as well as the increase in admission of patients with mental-health needs. Poor nurse-patient relationships have been reported by patients and in the media. The researchers experienced incidents of apparent misunderstandings during nurse-patient interactions whilst working in private general hospitals. No studies have been done regarding how nurses and care workers perceive a therapeutic relationship with patients in terms of the patients' emotional and mental-health needs. A quantitative, contextual and deductive study was conducted in three private general hospitals in Gauteng, South Africa with a purposive sample of 154 nurses and 30 care workers. Based on the concepts of a therapeutic relationship, empathy, positive regard, genuineness, concreteness and self-exploration, nurses and care workers' perceptions of facilitating a therapeutic relationship were self-assessed using five-point scales in a questionnaire. Data were analysed using descriptive statistics and non-parametric statistical techniques. Specific hypotheses were tested to identify whether statistically-significant differences existed between the perceptions of two or more groups of nurses and care workers. Results showed a general insensitivity and lack of awareness and reflection on the part of nurses and care workers with regard to the patients' emotional needs. When categories of nurses were compared, no statistically-significant differences were found between the perceptions of the various groups tested. There is a need for self-awareness, continued interpersonal skills training and supervision of nurses and care workers. A large percentage of the participants were younger than 40 years, subprofessional, with less than 10 years' experience as nurses or care workers. Private general hospitals should therefore equip all nurses and care workers with the necessary skills to facilitate a therapeutic relationship and to understand the emotional needs of all patients with both physical and emotional needs. Fasilitering van 'n terapetiese verhouding is 'n essensiёle vaardigheid in verpleging en veral in geestesgesondheid. Verpleegkundiges in private algemene hospitale is blootgestel aan die emosionele gevolge van fisiese siekte asook die toenemende toelating van pasiёnte met geestesgesondheidsbehoeftes. Swak verpleegkundige-pasiёnt verhoudings is deur pasiënte en in die media gerapporteer, terwyl die navorsers van oënskynlike misverstande tydens interaksies tussen verpleegkundiges en pasiënte bewus geword het tydens hulle werk in private algemene hospitale. Geen studies is gedoen oor hoe verpleegkundiges en versorgers hulle terapeutiese verhouding met pasiënte in terme van hulle emosionele en geestesgesondheidsbehoeftes ervaar nie. 'n Kwantitatiewe, kontekstuele en deduktiewe studie was in drie private algemene hospitale in Gauteng, Suid Afrika gedoen, met 'n doelgerigte steekproef van 154 verpleegkundiges en 30 versorgers. Verpleegkundige persepsies van die fasilitering van 'n terapeutiese verhouding gebaseer op die konsepte van 'n terapeutiese verhouding, empatie, positiewe agting, opregtheid, konkreetheid en selfondersoek is met self-assessering op 'n vyf-punt skaal van 'n vraelys bepaal. Data was geanaliseer met beskrywende statistieke en nie-parametriese tegnieke. Spesifieke hipoteses was getoets om te identifiseer of daar statistiese-betekenisvolle verskille tussen twee of meer kategorieё van verpleegkundiges bestaan. Resulte dui op 'n algemene ongevoeligheid en lae bewustheidsvlak en refleksie van verpleegkundiges en versorgers ten opsigte van die pasiёnte se emosionele behoeftes. Geen statistiese-betekenisvolle verskille is tussen die persepsies van die verskillende groepe in die navorsing gevind nie. Daar is 'n behoefte aan self-gewaarwording en voortdurende opleiding in interpersoonlike vaardighede en ondersteuning aan verpleegkundiges en versorgers. 'n Groot persentasie van die deelnemers was jonger as 40 jaar, sub-professioneel, met minder as 10 jaar ondervinding as verpleegkundiges. Private algemene hospitale moet dus alle verpleegkundiges en versorgers toerus met die nodige vaardighede om 'n terapeutiese verhouding te fasiliteer om al hulle pasiënte se fisiese en emosionele behoeftes te verstaan.